PENINGKATAN EFEKTIVITAS KERJA GURU MELALUI PENGUATAN KOMPETENSI PEDAGOGIK DAN IKLIM ORGANISASI - Sherly Maretha; Nandang Hidayat; Rais Hidayat (JURNAL MANAJEMEN PENDIDIKAN, 2021)
IMPROVING TEACHER WORK EFFECTIVENESS THROUGH PEDAGOGIC COMPETENCY STRENGTHENING AND ORGANIZATIONAL CLIMATE AT PRIVATE JUNIOR HIGH SCHOOLS IN CIBINONG, KABUPATEN BOGOR This study aimed to determine empirically the enhancement of teacher work effectiveness. The sampling in the study was 146 teachers who were determined by using proportional technique. The method used was the correlation method.  Hypothetical testing was carried out by using parametric statistical analysis in the form of simple and multiple linear regression analysis, where a significance level of α = 0.05. The research came up with three conclusions. Firstly, there was a positive and significant relationship between pedagogical competence and teacher work effectiveness where a random sampling correlation coefficient of ry1= 0.75.  Secondly, there was a positive and significant relationship between organizational climate and teacher work effectiveness where its correlation coefficient of ry2 = 0.56. Thirdly, there was a positive and significant relationship between pedagogic competence and organizational climate together with teacher work effectiveness where its correlation coefficient of ry.12 = 0.79. It could be concluded that teacher work effectiveness might be enhanced by strengthening the pedagogic competence and organizational climate.